Food Engineering interfaces - Aguilera, José Miguel; Simpson, Ricardo; Welti-Chanes, Jorge; Bermudez-Aguirre, Daniela; Barbosa-Canovas, Gustavo; SpringerLink (Online service). (New York Springer, 2011)
Food engineering interfaces is based on invited presentations from the 10th International Congress on Engineering and Food (ICEF 10) held in Viña del Mar, Chile in April 2008. Published as part of Springer?s Food Engineering Series, the book includes 28 chapters contributed by world leaders in food engineering and related disciplines. Topics include the food engineering world through the years, advanced thermal and nonthermal processing of food, the modeling of gastric digestion, applications of CFD in food processing, food safety engineering, food engineering economics, incorporation of fibers into foods, bioseparation of nutraceuticals, supercritical fluid extraction of essential oils, caking of food powders, advances in food microstructure analysis, and food packaging. Aimed at the food industry and academia, this book is an excellent resource for anyone interested in the state of the art and the upcoming developments in food engineering, where health and well-being are central.
Electronic reproduction.
Keywords: Food industry and trade; Electronic books